Amniotic Epithelial Cells: A New Tool to Combat Aging and Age-Related Diseases? - Di Germanio, Clara; Bernier, Michel; de Cabo, Rafael; Barboni, Barbara (Frontiers in Cell and Developmental Biology, 2016)
The number of elderly people is growing at an unprecedented rate and this increase of the aging population is expected to have a direct impact on the incidence of age-related diseases and healthcare-associated costs. Thus, it is imperative that new tools are developed to fight and slow age-related diseases. Regenerative medicine is a promising strategy for the maintenance of health and function late in life; however, stem cell-based therapies face several challenges including rejection and tumor transformation. As an alternative, the placenta offers an extraordinary source of fetal stem cells, including the amniotic epithelial cells (AECs), which retain some of the characteristics of embryonic stem cells, but show low immunogenicity, together with immunomodulatory and anti-inflammatory activities. Because of these characteristics, AECs have been widely utilized in regenerative medicine. This perspective highlights different mechanisms triggered by transplanted AECs that could be potentially useful for anti-aging therapies, which include: Graft and differentiation for tissue regeneration in age-related settings, anti-inflammatory behavior to combat “inflammaging”, anti-tumor activity, direct lifespan and healthspan extension properties, and possibly rejuvenation in a manner reminiscent of heterochronic parabiosis. Here, we critically discuss benefits and limitation of AECs-based therapies in age-related diseases.